2021
DOI: 10.14334/jitv.v26i4.2896
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Nest Preferences, and Forage Plants of Stingless Bees (Hymenoptera: Apidae: Meliponini) from West Halmahera, North Moluccas, Indonesia

Abstract: S<span lang="IN">urvey of stingless bee diversity, nesting preferences, and </span>forage<span lang="IN"> plants </span>was conducted in <span lang="IN">West Halmahera across 134 collection sites. </span>This research was<span lang="IN"> aimed to </span>determine species diversity, nesting preference and habitat, and domin<span lang="IN">a</span>nt for<span lang="IN">a</span>ge pl<span lang="IN">a</span>nts. There were three sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Tetragonula biroi was well known and first recorded in Papua islands, including the Indonesia Papuan [4], the recent distribution of the species was also recorded on Sulawesi Island by Indonesian researchers [16,18,19], and the first discovery of its presence in Halmahera island [28].…”
Section: Distribution and Endemic Species In Indonesiamentioning
confidence: 99%
See 3 more Smart Citations
“…Tetragonula biroi was well known and first recorded in Papua islands, including the Indonesia Papuan [4], the recent distribution of the species was also recorded on Sulawesi Island by Indonesian researchers [16,18,19], and the first discovery of its presence in Halmahera island [28].…”
Section: Distribution and Endemic Species In Indonesiamentioning
confidence: 99%
“…Wallacetrigona incisa was collected from Sulawesi [29], and it was found in South Sulawesi [19], and it was reported by [6] from Central Sulawesi and North Sulawesi. Rasmussen et al [9,30] informed that Lepidotrigona terminata and Tetragonula pagdeni were found in Sulawesi, and [19] reported their founding of the Stingless bee species distribution map in three tropical regions of Indonesia [7,19,24,28,32].…”
Section: Distribution and Endemic Species In Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…This can lead to propolis and cerumen displaying considerable variations in their chemical compositions. Salatnaya et al [172] investigated forage plants for the stingless bees of the genus Tetragonula in west Halmahera, Indonesia, and revealed the utilization of seventy-seven distinct plant species for nectar, pollen, and occasional sources. Resins are necessary for nest construction by stingless bees.…”
Section: Bee Species Effect On Propolismentioning
confidence: 99%